Archiving high-performance solid oxide fuel cells with titanate anode in sulfur- and carbon-containing fuels. (20th April 2018) - Shao, Lin; Si, Fengzhan; Fu, Xian-Zhu; Luo, Jing-Li
Abstract: Yttria doped strontium titanate (Y0.07 Sr0.89 TiO3, YST) material is synthesized using a conventional combustion method as anode for solid oxide fuel cells (SOFCs) in sulfur- and hydrocarbon-containing fuels. The YST perovskite exhibits good stability and chemical compatibility with yttria stabilized zirconia (YSZ) electrolyte in 0.5% H2 S-containing fuel at high temperatures. Moreover, the YST shows high electrical conductivity of 35 S cm −1  at 900 °C and the cell with this anode achieves a maximum power density of 200, 162 and 70 mW cm −2 when the anode is fed by 0.5% H2 S-containing hydrogen, syngas and methane fuels, respectively. More importantly, the cell shows negligible degradation in the sulfur-, carbon- and hydrocarbon-containing fuels. Thus, YST holds the promise as anode material for SOFCs, especially in high concentration sulfur-, carbon- and hydrocarbon-containing fuels.